Inverse polynomial matrix approximation - Kisielewicz, Jerzy W. (Zielona Góra: Uniwersytet Zielonogórski)
A computational algorithm for matrix C(z) which approximates the inverse of a given matrix Y(z) is described in this paper.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka